Combining culture‐dependent and culture‐independent molecular methods for the isolation and purification of a potentially novel anaerobic species from pit mud in a Chinese liquor distillery. Issue 4 (2nd November 2016) - Liu, Chaolan; Huang, Dan; Zhang, Wenxue
Abstract : Strain S12–27–1‐3‐5 (a potentially novel anaerobic species) with a 16S rRNA sequence homology of <97% was isolated and purified from pit mud by combining culture‐dependent and culture‐independent molecular methods, such as cloning of 16S rRNA, amplified rRNA restriction analysis, and denaturing gradient gel electrophoresis (DGGE). Phylogenetic analysis of the 16S rRNA gene indicated that strain S12–27–1‐3‐5 was related to Aminobacterium mobile strain ILE‐3 DSM 12262 T and Aminobacterium colombiense strain DSM 12261 T (95 and 96% similarity value, respectively). The results verified that cloning of the 16S rRNA was efficient to identify whether a potentially new bacterial taxon existed in impure isolates and that the DGGE method was a powerful tool for screening the target bacteria and for identifying duplicate strains. Therefore, the application of the culture‐independent molecular methods for the isolation and purification of a potentially novel species was effective. Strain S12–27–1‐3‐5 (= DSM 27871 = JCM 19605 = CICC 10731 T ) was an anaerobic amino acid‐degrading bacterium. The results of fermentation experiments demonstrated that strain S12–27–1‐3‐5 produced volatile fatty acids (VFAs) and the presence of Methanosarcina barkeri enhanced the generation of VFAs, which contribute to the aroma composition of Chinese liquor. This work could enrich the species resources and promote the development and utilization of an uncultured species. Copyright © 2016 The Institute of Brewing & Distilling